Concordance between responses to questionnaire scenarios and actual treatment to repair or replace dental restorations in the National Dental PBRN. Issue 11 (November 2015) - Heaven, Tim J.; Gordan, Valeria V.; Litaker, Mark S.; Fellows, Jeffrey L.; Rindal, D. Brad; Gilbert, Gregg H.; National Dental PBRN Collaborative Group, 1
Abstract Objective To quantify the agreement between treatment recommended during hypothetical clinical scenarios and actual treatment provided in comparable clinical circumstances. Methods A total of 193 practitioners in the National Dental Practice-Based Research Network participated in both a questionnaire and a clinical study. The questionnaire included three hypothetical scenarios about treatment of existing restorations. Clinicians then participated in a clinical study about repair or replacement of existing restorations. We quantified the overall concordance between their questionnaire responses and what they did in actual clinical treatment. Results Practitioners who recommended repair (instead of replacement) of more scenario restorations also had higher repair percentages in clinical practice. Additionally, for each of the three hypothetical scenario restorations, practitioners who recommended repair had higher repair percentages in clinical practice. Conclusions The questionnaire scenarios were a valid measure of clinicians' tendency to repair or replace restorations in actual clinical practice. Clinical implications: Although there was substantial variation in practitioners' tendency to repair or replace restorations, responses to questionnaire scenarios by individual practitioners were concordant with what they did in actual clinical practice.